Pengaruh fermentasi kombinasi jamur Pleurotus ostreatus dengan Trichoderma viridae terhadap kandungan nutrien dan aktivitas enzim selulase bungkil kopra - Umiani Hatta; Osfar Sjofjan; B. Sundu (Faculty of Animal Science, Universitas Brawijaya, 2014)
Copra meal is by-product of oil extraction that is produced in large quantity and relatively cheap in Indonesia. However, its high cellulose becomes obstacle for poultry diet. Two studies was conducted to optimize the utilization of copra meal by producing crude enzyme that matched with copra meal using solid state fermentation method with various doses and incubation time that mixed with Pleurotus ostreatus (PO) and Trichoderma viridae (TV). In the first study, copra meal was fermented with 4 levels of inoculum (L0 = no inoculum; L1 = 17.7 CFU/g of TV and 175.00 CFU/g of PO per kg of copra meal; L2 = 35.4 CFU/g of TV and 218.75 CFU/g of PO per kg of copra meal; L3 = 53.1 CFU/g of TV and 262.50 CFU/g of PO per kg of copra meal and 4 incubation time (W1= 4 days; W2 = 6 days; W3 = 8 days; and W4 = 10 days). Parameters measured were crude protein, crude lipid, crude fibre and gross energy. A completely randomized factorial design was used in the study. In the second study, crude enzyme was produced from the best results found in the first study. A method of Jacob and Prema (2006) was used to produce enzyme. Meanwhile, activity of cellulase was measured based on the method of Omojosola (2008). The results showed that factor of inoculum level was found significantly increased protein content and gross energy but decreased crude lipid and crude fibre of the mixed fungi-fermented copra meal. Incubation time did not affect protein content but significanly affected crude lipid, crude fibre and gross energy. Interactions between inoculum level and incubation time was found in crude lipid, crude fibre and gross energy contents of mixed fungi-fermented copra meal. Activity of cellulase was 0.71 g glucose/l. Keywords : Fermentation, Pleurotus ostreatus, Trichoderma viridae, inoculum level, incubation time, cellulase activity